SUFFERING FROM GOD? Reflections on I Peter 4:13–29 For Christians - Ludwig Beethoven Jones Noya; Bobby Kurnia Putrawan (Didache: Jurnal Teologi dan Pendidikan Kristen, 2022)
Suffering is an integral part of the status of a believer because the condition of following Christ is the Cross and leaving something, so suffering is the most important part of Christian teaching. Suffering is a fact that exists in every life in life without limits both believers and non-believers, but suffering for believers has a different meaning. The method used in this paper is a theological method with biblical theology studies. In I Peter 4: 13-29 the meaning of suffering for believers is explained, namely: first, as a test of faith to develop perseverance in the believer so that faith becomes stronger after going through purification and producing perseverance and the maturity of faith. Second, suffering for believers aims to glorify God, because through suffering and how to respond by staying grateful and joyful the Spirit of glory is in the believer. Third, suffering is God's will, because God is sovereign over all things and sustains all things with His powerful Word. In this study, the author examines and analyzes suffering for believers in terms of the theological meaning of suffering by exposing the text of I Peter 4: 13-27.   Penderitaan merupakan bagian integral dari status umat Kristenkarena syarat mengikut Kristus adalah salib dan meninggalkan sesuatu, maka penderitaan adalah bagian terpenting dari ajaran Kristen. Penderitaan merupakan fakta yang ada dalam setiap kehidupan dalam kehidupan tanpa batas baik yang beriman maupun yang tidak beriman, namun penderitaan bagi orang yang beriman memiliki arti yang berbeda. Dalam penelitian ini, penulis mengkaji dan menganalisis penderitaan bagi orang percaya ditinjau dari makna teologis penderitaan dengan memaparkan teks I Petrus 4:13-27.Metode yang digunakan dalam penulisan ini adalah metode teologis dengan kajian teologi biblika. Hasilnyadalam I Petrus 4:13-29 dijelaskan pengertian penderitaan bagi orang percaya, yaitu: pertama, sebagai ujian iman untuk mengembangkan ketekunan dalam diri orang percaya sehingga iman menjadi lebih kuat setelah melalui pemurnian dan menghasilkan ketekunan dan kedewasaan iman. Kedua, penderitaan bagi orang percaya bertujuan untuk memuliakan Tuhan, karena melalui penderitaan dan cara menyikapinya dengan tetap bersyukur dan bersukacita Roh kemuliaan ada pada orang percaya. Ketiga, penderitaan adalah kehendak Tuhan, karena Tuhan berdaulat atas segala sesuatu dan menopang segala sesuatu dengan Firman-Nya yang penuh kuasa.